2010
DOI: 10.3109/09286581003734878
|View full text |Cite
|
Sign up to set email alerts
|

Relationships in Glaucoma Patients Between Standard Vision Tests, Quality of Life, and Ability to Perform Daily Activities

Abstract: ADREV provides valid estimates of how visual loss due to glaucoma affects the ability to perform activities of daily living. Performance-based testing and quality of life evaluations are both independently important measures of health, which are related, but by no means the same.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 29 publications
5
63
0
5
Order By: Relevance
“…Similar with the previous study, 7 our data revealed significant associations between improvements of RLVT and changes of clinical measures [18][19][20][21] and less susceptible to confounding factors. 23,35 All these results of current study contribute to the validity of the RLVT as a potential assessment for cataract surgery outcomes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Similar with the previous study, 7 our data revealed significant associations between improvements of RLVT and changes of clinical measures [18][19][20][21] and less susceptible to confounding factors. 23,35 All these results of current study contribute to the validity of the RLVT as a potential assessment for cataract surgery outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…Pioneering studies has demonstrated that PBMs can be reliable and valid methods in assessing real-life visual ability. [13][14][15][16][17][18][19][20][21][22][23] Owing to its significance in visual hierarchy, PBMs of visual function is becoming an important part of researches on the real-life effects of visual diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,18,20,[23][24][25][26] However, little research has been done on Chinese population so far. Because PBMs are designed to understand how patients react in real-life activities, the 'tasks' that we selected should cover the most usual activities in daily life.…”
Section: Introductionmentioning
confidence: 99%
“…2,10,17 Based on the inherent limitations of clinical tests and self-report questionnaires, more recently there has been an upcoming interest in developing a complementary method for evaluation and outcome measures of visual function-the performancebased measures (PBMs) of visual function. 4,10,13,[18][19][20][21][22][23][24][25][26][27] Vision-specific PBMs take on actual performance of vision-related tasks. It involves presenting patients with commonly encountered tasks of daily life in a standardized format and getting a grade in accordance to their visual ability to complete the tests.…”
Section: Introductionmentioning
confidence: 99%